The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21670/ref.1802002
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Mexican SMEs insertion in the aerospace industry value chain, the Baja California case

Abstract: The goal of this article is to analyze the aerospace industry in Baja California, Mexico. The methodology is based on the application of an electronic questionnaire and face-to-face in depth interviews. Our results shows that the insertion of companies has been conditioned by several factors: the basic certification is only the first step; the real challenge is to find niches of opportunity and bargaining power to achieve a productive contract, which demands entrepreneurial, legal and economic skills. This ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Estudios sociales en la industria mexicana se desarrollan en las zonas fronterizas del país (Matus, Carrillo & Gomis, 2018;Hernández & Carrillo, 2018;Carrillo & Micheli, 2017;Brito & Carrillo, 2017;Gomis & Carrillo, 2016;Contreras, Plascencia & Carrillo, 2016;Lévesque et al, 2015;Carrillo, Hualde & Flacso-México, 2013;Hualde, 2001;Carrión & Hualde, 2013), en donde la concentración de la industria maquiladora es conveniente y se destaca por la inversión en tecnología de punta, manejo y control de calidad con altos estándares, incorporación de modelos de certificación y acentuada organización empresarial. En Carrillo y Hualde (2000) se describe una investigación sobre la industria maquiladora en la frontera, que reconoce a Ciudad Juárez y Tijuana como las ciudades fronterizas de mayor desarrollo industrial.…”
Section: Delimitación Geográfica Del Objeto De Estudiounclassified
“…Estudios sociales en la industria mexicana se desarrollan en las zonas fronterizas del país (Matus, Carrillo & Gomis, 2018;Hernández & Carrillo, 2018;Carrillo & Micheli, 2017;Brito & Carrillo, 2017;Gomis & Carrillo, 2016;Contreras, Plascencia & Carrillo, 2016;Lévesque et al, 2015;Carrillo, Hualde & Flacso-México, 2013;Hualde, 2001;Carrión & Hualde, 2013), en donde la concentración de la industria maquiladora es conveniente y se destaca por la inversión en tecnología de punta, manejo y control de calidad con altos estándares, incorporación de modelos de certificación y acentuada organización empresarial. En Carrillo y Hualde (2000) se describe una investigación sobre la industria maquiladora en la frontera, que reconoce a Ciudad Juárez y Tijuana como las ciudades fronterizas de mayor desarrollo industrial.…”
Section: Delimitación Geográfica Del Objeto De Estudiounclassified
“…In Baja California, some smes counting on access to required resources and capabilities entered the aerospace sector. The study of Hernández and Carrillo (2018) found that smes holding a certification may have the capacity to supply at different levels of the value chain after overcoming the obstacles of meeting the requirements of production and facing the complexity of management.…”
Section: Proposals Of Changes After Renegotiating Usmcamentioning
confidence: 99%
“…However, the insertion of Mexican companies in the aerospace industry has been scarce and little is known about the productive conditions, technological and digital tools of the Mexican companies that participate in this sector. [2][3][4] The viability of globalized production processes has received increased attention following events such as the Covid-19 pandemic, the war between Ukraine and Russia, as well as tensions between China and the United States. These events have highlighted the vulnerabilities of an intertwined global market, and shortages of components and materials have encouraged the creation of strategies to strengthen the security of supply chains.…”
Section: Introductionmentioning
confidence: 99%